Major Concepts in Spanish Feminist Theory - Johnson, Roberta, 1942- (Book collections on Project MUSE., 2019)
Major Concepts in Spanish Feminist Theory' is the first book in English to offer a substantial overview of Spanish feminist thought. It focuses on six concepts?solitude, personality, social class, work, difference, and equality?and distinguishes Spanish feminist theory from that of other countries. Roberta Johnson employs a chronological format to highlight continuity and polemics in Spanish feminist thinking from the eighteenth century to the present. She brings together arguments from well-known names such as Benito Jerónimo Feijoo, Concepción Arenal, Emilia Pardo Bazán, María Martínez Sierra, Carmen de Burgos, and Carmen Laforet, as well as less familiar figures such as the Countess Campo Alange María Laffitte and Lilí Álvarez, who defied restrictions on feminist activity during the Franco dictatorship to publish feminist books. The topics of difference and equality are explored, and the book recounts the long tension between theorists of each persuasion?a tension that erupted publicly during Spain?s democratic era. Each theorist?s arguments are laid out in straightforward, non-jargonistic prose, making this book a useful classroom tool for courses on Spanish women writers, Spanish culture, and cross-cultural feminist studies.